Практики сталого розвитку туризму у регіональному вимірі - Мельник, Ірина Леонідівна; Антоненко, Ірина Ярославівна; Вогулкіна, Дар’я Вікторівна (My University, 2024)
Підкреслено ключову роль розвитку туризму на засадах сталості та виділено екологічну складову як невід’ємну частину сталого туризму. Вивчено успішні практики сталого розвитку на прикладі природоохоронних територій, міст, регіонів, країн Європейського Союзу. Встановлено напрями реалізації практик (проєктів) сталого розвитку туризму: охорона природи, управління сталим туризмом, залучення місцевої громади, співпраця з іншими громадами, розвиток місць та доступність, стале управління енергією та ресурсами, цифровізація, боротьба та адаптація до змін клімату. Визначено, що в сучасному суспільстві впровадження нових ініціатив в туризмі потребує комплексного та системного підходу із залученням різних груп стейкхолдерів, особливо резидентів регіону, адже саме резиденти відчувають негативний вплив овертуризму. Досліджено втрати сфери туризму від війни в Україні. Підкреслено, що навіть в умовах війни Україна має потенціал для реалізації європейського досвіду з розвитку сталого туризму. The key role of tourism development on the basis of sustainability is emphasized. The ecological component is highlighted as an integral part of sustainable tourism. Sustainable development in the field of tourism emphasizes the need for effective and rational interaction between all participants in the market, since the analysis of sustainable development covers the process of preserving and reproducing the nation's genetic fund, ensuring rights and freedoms, environmental protection, creating conditions for the restoration of the biosphere and its local ecosystems, reducing anthropogenic. Impact on the environment and harmonization of development. Successful sustainable tourism practices development was studied on the example of environmental territories, cities, regions, countries of the European Union. The directions of implementation of sustainable tourism practices development of tourism were established: nature protection, management of sustainable tourism, involvement of local community, cooperation with other communities, development of places and accessibility, sustainable management of energy and resources, digitalization, struggle and adaptation to climate change. It is determined that today, the introduction of new initiatives in tourism requires a comprehensive and systematic approach with the involvement of different groups of stakeholders, especially residents of the region, because overtourism have a negative impact of residents. Sustainable tourism practices development today include investments in local communities for the formation of modern manufacturers of tourist services; development of ecological tourism through the travel of nature conservation areas; development of rural tourism through vacation in small cities in estates; popularization of cultural tourism, including historical, cultural, gastronomic and guilty, etc.; introduction of digital tools for energy-saving use of resources, complex promotion of destinations on all digital platforms, etc.; marketing campaigns aimed at raising a responsible tourist. The loss of tourism from war in Ukraine has been investigated. It is emphasized that even in the war, Ukraine has the potential for the implementation of European experience in the development of sustainable tourism.
Keywords: сталий туризм; овертуризм; практики сталого туризму; overtourism; sustainable tourism practices; regional dimension; Ukraine; Ukraine